The Effectiveness Of Group Guidance Using Acceptance And Commitment Therapy (Act) Techniques To Increase Students' Physical Self-Acceptance At Imelda Junior High School - Anissa, Nur; Siregar, Alfin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to examine the implementation of group counseling services using the Acceptance and Commitment Therapy (ACT) technique to improve students’ physical self-acceptance. The research employed a Quasi-Experimental approach with a Pre-Test Post-Test Control Group Design. The participants consisted of 16 eighth-grade students of SMP Imelda Medan, divided into two groups: 8 students in the experimental group and 8 students in the control group, selected using purposive sampling. The results of the Paired Sample T-Test showed a significant difference between the experimental and control groups, with a significance value of 0.000 < 0.05. Thus, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This indicates that group counseling using the ACT technique is effective in improving students' physical self-acceptance. The average pre-test score in the experimental group was 79.13, which increased to 102.75 in the post-test. Meanwhile, the control group’s pre-test average was 78.25 and post-test average was 85.75. The increase in post-test scores indicates a significant improvement in physical self-acceptance